2005
DOI: 10.1128/jcm.43.9.4801-4806.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rapid Dipstick and Latex Agglutination Tests and Enzyme-Linked Immunosorbent Assay for Serodiagnosis of Amebic Liver Abscess, Amebic Colitis, and Entamoeba histolytica Cyst Passage

Abstract: A homemade enzyme-linked immunosorbent assay (ELISA) and a dipstick assay (Dipstick) for the detection of anti-Entamoeba histolytica antibodies in serum were developed and evaluated together with a commercially available latex agglutination test (LAT; Laboratoires Fumouze) for their use in serodiagnosis of amebiasis. The sensitivity of these assays was evaluated with sera from 27 patients with radiologically proven, cellulose acetate precipitation (CAP) test-positive amebic liver abscess, 7 patients with paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Latex agglutination test (LAT) has been widely used in medicine for detection of substances (hormones, drugs or proteins) in biological fluids including saliva, urine, or blood (32)(33)(34)(35)(36)(37). Because of many advantages over other tests, that is, fast, easy, highly selective, and inexpensive, LAT is applied to detect over 100 infectious diseases (38)(39)(40).…”
Section: Latex Agglutination Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Latex agglutination test (LAT) has been widely used in medicine for detection of substances (hormones, drugs or proteins) in biological fluids including saliva, urine, or blood (32)(33)(34)(35)(36)(37). Because of many advantages over other tests, that is, fast, easy, highly selective, and inexpensive, LAT is applied to detect over 100 infectious diseases (38)(39)(40).…”
Section: Latex Agglutination Testmentioning
confidence: 99%
“…6. This approach is applicable to mono and polyvalent antigens, that is, drugs, hormones, and proteins (38). Currently, many infectious diseases including leptospirosis, amebiasis, and Entamoeba histolytica Cyst Passage can be diagnosed with high sensitivity and specificity (>90%) by using the indirect LAT (32,34,44). …”
Section: Indirect Latex Agglutination Testmentioning
confidence: 99%
“…[ 10 11 ] Hence, rapid serodiagnosis for suspected cases of amebiasis is often an important tool in clinical decision making and can be of help in the reduction of the costs of additional treatment and prolonged hospital stay. [ 12 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Plate ELISA is successfully applied to the serodiagnosis of amoebiasis. (Rosenblatt et al, 1995, Punthuprapasa et al, 2001, Haghighi et al, 2005) Dot ELISA for serodiagnosis of amoebiasis is also reported (Mahajan et al, 1989: Lopez et al, 1991, Yamura et al, 2003, Van Doorn et al, 2005, Dhanalakshmi et al, 2016. The present study was undertaken to develop Intact Parasite Antigen-ELISA (IPA-ELISA)test in the diagnosis of intestinal and extraintestinal amoebiasis and also to determine its sensitivity and specificity in comparision to Plate-ELISA, Dot Elisa.The relative merits of tests were also found out for clinical and epidemiological sur-vey of amoebiasis.…”
Section: Introductionmentioning
confidence: 99%